The effect of an educational curriculum according to agility exercises on the accuracy of handball scoring - NajiZaidan, Huda; TalalAbdulla, Ali (International Journal of Psychosocial Rehabilitation, 2020)
Handball is one of the team games that is characterized by intense competition during its practice between the players of the two competing teams, which depends on the good performance of technical skills and outstanding physical fitness for handball practitioners of both sexes, and agility is one of the basic requirements. And modern methods in the process of teaching basic handball skills, note the low level of students’ performance in some basic handball skills, which is reflected in the poor level of the game in, and this is a problem that must be addressed in order to study, analyze and find the scientific solutions necessary to address it, and through the use of physical exercises and skill according to the agility method in the accuracy of shooting with the hand reel, The importance of the research lies in the development and application of a set of special and diverse exercises and the implementation of these exercises using the effect of an educational curriculum according to agility exercises in the accuracy of handball scoring. In light of the conclusion, the researchers recommend 1- Benefiting from agility exercises in developing handball accuracy skills 2- Using agility exercises to develop other activities